PENERAPAN MODEL PEMBELAJARAN INDEX CARD MATCH DALAM MENINGKATKAN HASIL BELAJAR IPA KELAS III DI MI NURUL ULUM TULUNGAGUNG: Indonesia - Faradhila Putri; Apri Wahyudi; Abdul Hamid (Al-Ibda: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
AbstractThis research is motivated by the low learning outcomes of IPA subjuc in MI Nurul Ulum Tulungagung, Gadingrejo subdistrict, Pringsewu District. This research is a class action research (ptk) through the application of the index card match learning model which is carried out twice a cycle in class III students (25 students). Instruments used were interviews, documentation, teacher and student observation sheets, student worksheets, the factor investigated were student learnig outcomes, teacher and student activities. The procedure of this study starts from planning, observation, action, evaluation, analysis and reflection. The results of this study indicate that the application of the index card match learning model in class III MI Nurul Ulum can significantly improve student learning outcomes. Pra cycly activities show that overall student learning outcomes only reach 35,52%, after taking action in cycle 1 using the indec card match learning method student learning outcomes have increased student learning completeness by 60,21%, then proceed to the cycle II action and have ancreased completeness by 87,50%.Keyword : learning, index card match, learning outcome